Comparison of Relational Database Modeling Performance based on Number of Normalized Entities: - - Yunianto, Dika Rizky; Yudistira Eka Putra; Cahya Rahmad (SMARTICS Journal, 2023)
The database is the most important part of the development of a software. Management of data storage in the database is very important because the amount of data stored is increasing and varied. Thus requiring increased storage capacity and increased processing time. One form of database used in software is a relational database. Relational database modeling to reduce storage capacity can be circumvented by normalizing the database. From the experimental results, database normalization has an effect on the number of entities. So that the storage capacity and processing time in data processing are also affected by the normalization of the database. The more the number of entities will cause the more time needed in data processing.